Control de pulgón (Toxoptera citricida L.) en el cultivo de mandarinero mediante tres insecticidas en la Comunidad San José, Cantón Pimampiro, Provincia de Imbabura - Sarchi Chandi, Cristhian Eduardo (2018)
SUMMARY The attack of aphid in the mandarinerous crops produces representative damages in the vegetative buds and floral buds which causes low yields in the production and decrease of the profitability, this occurs due to ignorance of the phenology of the crop and the biology of the aphid. The present study was conducted because it could be evidenced the presence of aggressive attacks of this pest in mandarinerous crops, which feeds on new shoots producing honeydew that accumulates on the leaves favoring the development of fungi and loss of plants by transmission of virus. To do this, for every two trees the insecticides were applied: profenofos, imidacloprid and acephate, and the aphid attack was monitored in two trees in which no control was made, the monitoring was carried out 8 days before and 8 days after to verify the percentage of control of each of the insecticides and their efficiency. As a result, it was found that the profenofos insecticide is the most effective at the time of application, using a dose of 0.125% reached a control of 96.35%. Therefore, untreated trees have a scale of 4 with atrophied shoots, rolled leaves while trees that received the application of profenofos had a rating of 0.63. In advance, it is recommended to citrus farmers make preventive controls of aphid with the profenofos product at 0.125% to avoid economic losses in their crops.